Position of Russia and France on the Global Food Market: Trends and Prospects - V N Kholina (RUDN Journal of Economics, 2011)
Food production and world trade determines countries’ economic and political security and draws constant attention of the international community. A growing number of hungry and malnourished people in the world (especially in the less developed countries), high share of import in consumption in some East European countries and Russia makes international food trade an element of the “big” policy. In many ways it was triggered by the rise of food prices, which began in 2007. In such conditions regional imbalance in production and international food trade has increased. A role of food in the merchandise export of regions and key countries in the world, Russia’s position on the global food markets (as a major importer of meat and milk and exporter of wheat) as well as the EU’s (as the world leader in food export and import) and France’s (as an important food exporter) is analyzed in the article. It is also given a comparative analysis of production’s economic efficiency.